Changes in plasma brain natriuretic peptide in conventional or direct stenting - Khan, Saidur Rahman; Kurtoglu, Nuri; Benli, Fehime; Toprak, Ahmet; Agirbasli, Mehmet; Oktay, Ahmet (University Heart Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Direct coronary stenting without balloon predilatation may cause lower postprocedural minor myocardial injury in comparison to conventional stenting with balloon predilatation.Plasma brain natriuretic peptide (BNP) is increased in acute myocardial ischaemia. 40 patients with single vessel and single lesion coronary artey disease who underwent elective stent implantation were divided into Group I (n=20) treated with direct coronary stenting (DS) and Group II (n=20) with conventional stenting (CS). Blood samples for Troponin I and CK-MB measurement were obtained at baseline, just after the intervention procedure, 6 hours after and 12 hours after stenting and for BNP levels at baseline, 6 hours and 12 hours after stenting. In Group II there was a significant increase in Troponin I level 12 hours after the procedure (baseline 0.033 ± 0.028 ng/ml vs. 0.084 ± 0.085 ng/ml; p < 0.05).Plasma BNP level in Group I decreased significantly both in base line vs. 6 hours after procedure and baseline vs. 12 hours after procedure (105.2 ± 73.7 pg/ml vs. 81.3± 67.1 pg/ml; p < 0.05 and 105.2 ± 73.7 pg/ml vs. 89.9 ± 62.3pg/ml ; p < 0.05 respectively). With direct stenting BNP levels decreased significantly with no change in Troponin I level, while with conventional stenting Troponin I levels increased significantly. Key words: Brain natriuretic peptide, Direct stenting, Conventional stenting. doi:10.3329/uhj.v4i2.2066 University Heart Journal Vol. 4 No. 2 July 2008 p9-15